Integrating Project Portfolio With Business Strategy: Imagineering - Dal Maso, Cesar Buaes; da Silva, Wanderlei Marinho; de Mello, Pedro Carvalho; Arruda Filho, Norman de Paula (Future Studies Research Journal: Trends and Strategies, 2015)
Aligning project management to the strategy of a big company is a difficult job. Through Imagineering (the business department and project management program), The Walt Disney Company has done this alignment in an exemplary way. Using a theoretical investigation, this study analyzed the Imagineering as a reference in strategic management of global projects through Disney´s business portfolio, a global benchmarking and with Malmberg et al. (2010) as a company guide. As the main results of the correlations carried out, it was noted that the Imagineers who work in project teams apply tools and techniques with a strategic vision focused on differentiation, generating value, and mixing imagination with technical capacity. The Blue Sky department and its integrated units make possible the creation and deployment of the attractions, the theme parks, hotels, resorts and the Disney sea cruises, demonstrating in this way, to be a highly effective project management office.